(untitled) (Journal of Global Humanities and Social Sciences, 2025)
Interaction is a function that is considered more and more in the development of modern society. It originates from the inspiration and support of science and technology, which makes people pay more and more attention to the interactive significance of various services. Interaction can enhance the sense of participation and deepen the experience, and intelligent interaction design is the key to forming this experience. As the condensation and exhibition of museum culture, it creates a concentrated expression space for the connotation of a region or a city, and how to use the interaction design function to make it express as much as possible is the focus of this article. This article will discuss its application methods and think about its application value by combining the specific cases of interaction design and interactive experience in museum situations.